Comparative Proteomic Studies of Yersinia pestis Strains Isolated from Natural Foci in the Republic of Georgia - Nozadze, Maia; Zhgenti, Ekaterine; Meparishvili, Maia; Tsverava, Lia; Kiguradze, Tamar; Chanturia, Gvantsa; Babuadze, Giorgi; Kekelidze, Merab; Bakanidze, Lela; Shutkova, Tatiana; Imnadze, Paata; Francesconi, Stephen C.; et al. (Frontiers in Public Health, 2015)
Yersinia pestis, the causative agent of plague, is a highly virulent bacterium responsible for millions of human deaths throughout history. In the last decade, two natural plague foci have been described in the Republic of Georgia from which dozens of Y. pestis strains have been isolated. Analyses indicate that there are genetic differences between these strains, but it is not known if these differences are also reflected in protein expression. We chose four strains of Y. pestis (1390, 1853, 2944, and 8787) from the National Center for Disease Control and Public Health collection for proteomic studies based on neighbor-joining tree genetic analysis and geographical loci of strain origin. Proteomic expression was analyzed using two-dimensional gel electrophoresis and mass spectrometry. Select Y. pestis strains were grown under different physiological conditions and their proteomes were compared: (1) 28°C without calcium; (2) 28°C with calcium; (3) 37°C without calcium; and (4) 37°C with calcium. Candidate proteins were identified and the differences in expression of F1 antigen, tellurium-resistance protein, and outer membrane protein C, porin were validated by Western blotting. The in vitro cytotoxicity activity of these strains was also compared. The results indicate that protein expression and cytotoxic activities differ significantly among the studied strains; these differences could contribute to variations in essential physiological functions in these strains.